2020
DOI: 10.11646/zootaxa.4845.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotepuibasis gen. nov., a new monotypic genus of Coenagrionidae from Colombian Amazon (Odonata: Zygoptera)

Abstract: Pseudotepuibasis gen. nov. is erected for P. garrisoni sp. nov. from the Colombian Amazon (December 2015, Caquetá Department, Solano Municipality, Araracuara, Guacamayo Guard, -72.2497, -0.6308, L. Pérez leg.). Male and female of this new genus are described and illustrated, cerci of male with a ventrobasal spur for which it is considered in the tribe Teinobasini, close to Tepuibasis De Marmels, 2007 and Austrotepuibasis Machado & Lencioni, 2011, by its color pattern and cerci morphology; and close to Lept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Knowledge of the order Odonata in the Colombian Amazon has greatly increased in the last decade. Species new to science have been discovered (Bota-Sierra et al 2015;Pérez-Gutiérrez 2019;Stand-Pérez & Pérez-Gutiérrez 2020;Flórez et al 2023) and new records have been made for species previously found only in neighbouring countries such as Brazil, Peru, or Venezuela (Bota-Sierra et al 2015;Stand-Pérez et al 2021;Cano-Cobos et al 2023). These studies highlight the great diversity of this region and encourage researchers to continue exploring it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the order Odonata in the Colombian Amazon has greatly increased in the last decade. Species new to science have been discovered (Bota-Sierra et al 2015;Pérez-Gutiérrez 2019;Stand-Pérez & Pérez-Gutiérrez 2020;Flórez et al 2023) and new records have been made for species previously found only in neighbouring countries such as Brazil, Peru, or Venezuela (Bota-Sierra et al 2015;Stand-Pérez et al 2021;Cano-Cobos et al 2023). These studies highlight the great diversity of this region and encourage researchers to continue exploring it.…”
Section: Discussionmentioning
confidence: 99%
“…Species new to science have been discovered ( Bota-Sierra et al . 2015; P éRez-Gutiérrez 2019; Stand-Pérez & Pérez-Gutiérrez 2020; Flórez et al . 2023) and new records have been made for species previously found only in neighbouring countries such as Brazil, Peru, or Venezuela ( Bota-Sierra et al .…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic diversity observed in this rapid assessment clearly justifies continued taxonomic inventories of insect taxa within key geographical areas (hotspots) ( Mound 1998). Since the preliminary list of Odonata for the Colombian Amazon was published ( Bota-Sierra et al 2015), the number of new records has increased due to increased surveying and recent taxonomic studies ( Bota-Sierra et al 2018a, 2018b; Stand-Pérez et al 2019; Stand-Pérez & Pérez-Gutiérrez 2020; González-Gómez et al 2020). No doubt further inventories will further augment the known species for the country.…”
Section: Discussionmentioning
confidence: 99%
“…We present a list of damselflies and dragonflies from the Southern Serranía de Chiribiquete National Natural Park. This includes 17 new species records for the country thus augmenting the total number of species from 452 ( Amaya-Vallejo et al 2018; Bota-Sierra et al 2018a, 2018b, 2019a, 2019b; Garrison 2019; Pérez-Gutiérrez 2019; Stand-Pérez et al 2019; Gonzáles-Gómez et al 2020; Sierra & Novelo-Gutiérrez 2020; Stand-Pérez & Pérez-Gutiérrez 2020; Amaya-Vallejo et al 2021; Novelo-Gutiérrez & Bota-Sierra 2021) to 468. We provide a map of localities visited, field photographs and habitus scans for the new records, and comment on the significance of the area for conservation.…”
Section: Introductionmentioning
confidence: 99%